Teen dating violence: predictive role of sexism and the mediating role of empathy and assertiveness based on gender - Villanueva-Blasco, Víctor José; Iranzo, Begoña; Mateu-Mollá, Joaquín; Carrascosa, Laura; Gómez-Martínez, Sandra; Corral-Martínez, Marta; Mitjans, Mª Teresa; Hernández-Jiménez, Mª Jesús (Frontiers in Psychology, 2024)
Background Despite efforts to prevent dating violence among adolescents, it remains a major problem with multiple negative consequences. Sexist beliefs, empathy, and assertiveness influence teen dating violence (TDV) with potential gender differences. Objectives (1) Determine gender disparities in TDV perpetration and victimization, including relational, verbal-emotional, and physical aspects, as well as roles; (2) Analyze gender variations in sexism, empathy, assertiveness, and their relationship with TDV; (3) Establish a predictive model of sexism in TDV with empathy and assertiveness as mediators for both genders. Participants and setting A sample of 862 secondary school students (50.2% females, 49.8% males; mean age: 14.1 years) from diverse regions in Spain participated. Methods TDV was measured using the Conflict in Adolescent Dating Relationships Inventory (CADRI) in a cross-sectional study. Sexism, empathy, and assertiveness were assessed using the Ambivalent Sexism Inventory (ASI), Interpersonal Reactivity Index (IRI), and Assertiveness Inventory for Students Questionnaire (AISQ), respectively. Results Females exhibited higher TDV perpetration, specifically verbal-emotional TDV. Males showed more relational TDV and hostile sexism, while no benevolent sexism differences were observed. Mediation models demonstrated sexism, assertiveness, and empathy as individual predictors of TDV, with varying mediation effects. Personal distress partially mediates the link between sexism and TDV perpetration or victimization in males, while practical personal ability mediates between sexism and TDV perpetration in females. Conclusion Sexism predicts both perpetration and victimization in TDV, linked to empathy and assertiveness. Notably, specific dimensions of empathy and assertiveness mediate the connection between sexism and TDV, displaying gender-specific patterns. Preventive measures should consider personal distress in male perpetrators/victims and practical personal ability in female perpetrators.